Effectiveness of Financial Management in Private Schools to Achieve Excellent Accreditation: Case Study at SD IT Al-Fitrah - H. Soro , Suharyanto; Rosalina, Anindya; Faridah , Faridah (Civiliza Publishing, Indonesia., 2025)
Study This aiming For analyze implementation strategy management financing at SDIT Al-Fitrah and evaluate the impact to achievement of status as school featured . Study This use approach studies case qualitative for get deep understanding​ about practices financing applied by the school. Data is collected through technique interview in-depth, observation participatory, and review relevant documentation Data analysis was performed with using interactive models from Miles and Huberman, which includes stages data reduction, data presentation, and extraction as well as verification Conclusion. Research results show that practice needs - based financing​ real (needs-based budgeting), involvement active parents and community, as well as Work The same with the business world and institutions external, including utilization technology information, in significant support effectiveness management finance school. Strategies the impact positive on improvement quality learning, provision adequate facilities and infrastructure, as well as strengthening image and reputation school as institution superior and trusted education. In general overall, can concluded that management planned financing​ with good, good natured participatory, and implemented in a way transparent can become pillar main in build school quality, empowered private sector competition high, and trusted by the community. Findings This give implications practical for manager school private other in develop sustainable and oriented financing models​ quality.